Answer:
7/30
Step-by-step explanation:
-3/9 * -56/80
-3/9= -1/3
-56/80 = -7/10
-1/3(-7/10)
1(7) / 3(10)
7/30 or 0.2333
Answer:
(2, - 3 )
Step-by-step explanation:
Given the 2 equations
y = - 3x + 3 → (2)
y = - 9x + 15 → (2)
Substitute y = - 3x + 3 into (2)
- 3x + 3 = - 9x + 15 ( add 9x to both sides )
6x + 3 = 15 ( subtract 3 from both sides )
6x = 12 ( divide both sides by 6 )
x = 2
Substitute x = 2 into either of the 2 equations and solve for y
Substituting into (1)
y = - 3(2) + 3 = - 6 + 3 = - 3
solution is (2, - 3 )
<span>We have to find the product : ( 9 t - 4 ) ( - 9 t - 4 ) = - ( 9 t - 4 ) ( 9 t + 4 ) After that we can use the difference of squares. The formula is: ( a + b ) ( a - b ) = a^2 - b^2. In this case: - ( 9 t - 4 ) ( 9 t + 4 ) = - ( 81 t^2 - 16 ) = - 81 t^2 + 16 . Answer: B ) - 81 t^2 + 16.</span>
Answer:
C
Step-by-step explanation:
Sorry if I’m wrong but I think I’m right